Analisis Tingkat Hunian Kamar Dalam Hubungannya Dengan Profitabilitas Pada Hotel Ranggonang Sekayu - Candra Romanda (Universitas Malahayati, 2016)
The high level of occupancy of a hotel will indirectly affect profitability. Hotel Ranggonang Sekayu have common customers and the Department of Local Government Agencies or Musi Banyuasin. The results were obtained an average occupancy rate of hotel rooms Ranggonang Sekayu in the year 2012 - 2014 are likely to fall. Factors that cause fluctuations and a decline in the occupancy rate for the condition of Hotels many facilities are damaged, poorly-maintained, and facilities that do not meet the standards. The ratio of profit margin and net profit Hotel Ranggonang Sekayu years 2012 - 2015 fluctuated. This is because a lot of the District Government receivables uncollectible Banyuasin so that a burden is the burden of bad debts